2020
DOI: 10.1002/micr.30668
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of overall and disease‐free survival in patients with free flaps for oral cancer resection

Abstract: Purpose Sarcopenia is characterized by depletion of skeletal muscle mass (SMM) and can cause increased postoperative complication in free flap procedure. One of the most important considerations while deciding the indication of the procedure is patients' survival. This study aimed to verify the relationship between low SMM and survival in patients who undergo oral cancer resection using free flap. Methods SMM was evaluated using the skeletal muscle index (SMI cm2/m2), which was defined using cross‐sectional ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…We screened the titles and abstracts of these studies and identified 83 potentially eligible studies. The full-text versions of these 83 studies were then inspected according to the exclusion criteria, and 18 studies involving 3,233 patients were determined to be eligible for inclusion in this study [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Table 1). In these 18 studies, seven investigated patients treated with surgery [17, 20, 25-27, 31, 32] and 10 investigated patients treated with RT [15, 16, 18, 19, 21-24, 29, 30].…”
Section: Literature Search Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…We screened the titles and abstracts of these studies and identified 83 potentially eligible studies. The full-text versions of these 83 studies were then inspected according to the exclusion criteria, and 18 studies involving 3,233 patients were determined to be eligible for inclusion in this study [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Table 1). In these 18 studies, seven investigated patients treated with surgery [17, 20, 25-27, 31, 32] and 10 investigated patients treated with RT [15, 16, 18, 19, 21-24, 29, 30].…”
Section: Literature Search Results and Study Characteristicsmentioning
confidence: 99%
“…[31] used the psoas muscle mass index, and the study by Choi et al [21] used the skeletal muscle area of the neck. The remaining 16 studies used skeletal muscle mass index (SMI), with seven [15,18,23,25,[27][28][29] and nine [16,17,19,20,22,24,26,30,32] studies measuring the muscle area at the L3 and C3 spine levels, respectively. Eight studies [16, 18, 19, 22-24, 29, 30] in the RT group and six studies [17,20,[25][26][27]31] in the surgery group reported stage distribution between stage I, II and stage III, IV disease.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations